2013
DOI: 10.1007/s11103-012-0006-z
|View full text |Cite
|
Sign up to set email alerts
|

Sugar starvation- and GA-inducible calcium-dependent protein kinase 1 feedback regulates GA biosynthesis and activates a 14-3-3 protein to confer drought tolerance in rice seedlings

Abstract: Germination followed by seedling growth constitutes two essential steps in the initiation of a new life cycle in plants, and in cereals, completion of these steps is regulated by sugar starvation and the hormone gibberellin. A calcium-dependent protein kinase 1 gene (OsCDPK1) was identified by differential screening of a cDNA library derived from sucrose-starved rice suspension cells. The expression of OsCDPK1 was found to be specifically activated by sucrose starvation among several stress conditions tested a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 64 publications
5
72
0
Order By: Relevance
“…Our results suggested that OsCPK9 is a positive regulator of the responses to drought, osmotic, and dehydration stresses (Figure  2; Additional file 1: Figure S2 and S3). These results are consistent with those of previous studies on some other CDPK genes that positively regulate drought stress tolerance [18,24,28]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results suggested that OsCPK9 is a positive regulator of the responses to drought, osmotic, and dehydration stresses (Figure  2; Additional file 1: Figure S2 and S3). These results are consistent with those of previous studies on some other CDPK genes that positively regulate drought stress tolerance [18,24,28]. …”
Section: Discussionsupporting
confidence: 93%
“…SPK is involved in regulating the metabolic pathway responsible for the conversion of sucrose into storage starch in immature seeds [27]. OsCDPK1 negatively regulates the expressions of enzymes required for GA biosynthesis and seed size, but positively regulates drought stress tolerance through the14-3-3 protein [28]. However, it is unclear whether CDPKs play a role in regulating spikelet fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium-dependent seed-specific protein kinase (SPK) functions in the regulation of the metabolic pathway responsible for sucrose to storage starch conversion in immature seeds, thus making it as a crucial regulator of seed development in rice (Asano et al 2002). OsCDPK1 was found to be a negative factor of GA biosynthesis and seed size in rice (Ho et al 2013). Recently, OsCPK9 was reported to improve pollen viability, thereby increasing spikelet fertility in rice (Wei et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Free Ca ion within cell is a second messenger for conveying internal and external signals by Ca sensors that subsequently regulate diverse cellular processes in plants [17]. Calmodulin (CaM) and calcium-dependent protein kinase (CDPK), two major types of Ca sensor, play important roles in Ca signaling and further response to diverse stresses in plants [51]. Saijo et al [52] found that over-expression of OsCDPK gene enhanced tolerance to cold, salt and drought in transgenic rice.…”
Section: Discussionmentioning
confidence: 99%